2002
DOI: 10.1016/s0378-1097(02)00894-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hox genes and analysis of their transcription in the unicellular cyanobacterium Gloeocapsa alpicola CALU 743 growing under nitrate-limiting conditions

Abstract: The unicellular non-N 2 -fixing cyanobacterium Gloeocapsa alpicola CALU 743 contains a bidirectional hydrogenase. Parts of all structural genes, encoding the hydrogenase, were identified, cloned and sequenced. When comparing the sequences with analogous sequences from other cyanobacteria the highest similarity was observed with hox genes from Synechocystis sp. PCC 6803. The hydrogenase activity increased considerably when the cells were grown aerobically in a medium with limiting concentrations of nitrate. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 15 publications
(22 reference statements)
0
16
0
1
Order By: Relevance
“…Anaerobic induction of the two hox gene clusters. It has been demonstrated that anaerobic conditions induce higher transcription levels of hoxH transcript in the filamentous, heterocystous Nostoc muscorum and Anabaena variabilis ATCC 29413 (6,46). In the present study, when cells of Nostoc sp.…”
Section: Resultsmentioning
confidence: 45%
See 2 more Smart Citations
“…Anaerobic induction of the two hox gene clusters. It has been demonstrated that anaerobic conditions induce higher transcription levels of hoxH transcript in the filamentous, heterocystous Nostoc muscorum and Anabaena variabilis ATCC 29413 (6,46). In the present study, when cells of Nostoc sp.…”
Section: Resultsmentioning
confidence: 45%
“…3), a result which is in agreement with physiological data reported earlier (19,20). It has long been demonstrated that microaerobic/ anaerobic conditions influence the bidirectional hydrogenase activity in heterocystous cyanobacteria (6,19,20,39,44,46). However, this is the first time that it is demonstrated that the anaerobically induced activity of the enzyme is in parallel with an increase in transcription of the two hox operons in Nostoc sp.…”
Section: Vol 73 2007mentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, a bi-directional enzyme (encoded by hoxEFUYH) may be present which, depending on the growth conditions, may display the capacity of both producing and consuming H 2 (Lambert & Smith, 1981;Houchins, 1984;Schmitz et al, 2002;Tamagnini et al, 2002). All cyanobacteria examined so far contain an uptake, a bi-directional or both the hydrogenases (Schmitz et al, 1995(Schmitz et al, , 2002Boison et al, 1996;Tamagnini et al, 2000Tamagnini et al, , 2002Sheremetieva et al, 2002;Schütz et al, 2004). Moreover, the uptake-type enzyme has been found in all nitrogen fixing cyanobacterial strains studied to date (Carrasco & Golden, 1995;Oxelfelt et al, 1998;Happe et al, 2000;Tamagnini et al, 2000Tamagnini et al, , 2002Schütz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Lactate was found to be the major excreted fermentation product of wild-type (WT) cells, and the enzyme producing D-lactate, which competes with hydrogenase for reducing equivalents, was eliminated genetically. Nitrate deprivation (25) and nickel supplementation (3) were previously shown to increase hydrogen yield in other strains, and therefore these treatments were examined in combination with the ldhA mutation to optimize conditions for hydrogen production. The ldhA mutant has dramatically redistributed fermentative fluxes in comparison to WT cells and a higher NAD(P)H/NAD(P) ϩ ratio and up to 5-fold higher hydrogen production than those of WT cells.…”
mentioning
confidence: 99%